Brevis oratio penetrat celum: Proverbs, Prayers, and Lay Understanding in Late Medieval England - Bennett, Alastair (New Medieval Literatures, 2012)
Abstract This article explores the different interpretations of the phrase ‘Brevis oratio penetrat celum’, ‘A short prayer pierces heaven’, that circulated in late medieval England. It argues that the phrase was often used to think about the efficacy of laypeople’s prayer in a context where laypeople were increasingly able to access traditionally clerical knowledge. The article considers texts that identify the phrase as a ‘comoun prouerbe’, texts that link it to the Paternoster, and texts that explain it with reference to academic discourse about atomism, before turning to Piers Plowman, where the phrase provokes some complex reflections on the way that different forms of knowledge might be internalized and articulated as devotion.